Perlindungan Konsumen terhadap Overclaim Produk Skincare - Adinda Ayu Puspita Kuncoro; M. Syamsudin (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is based on the protection of consumers over the use of overclaims in skincare advertising that can harm consumers, such as overclaiming the percentage of content and the use of prohibited claims. This research discusses the legal protection of overclaims in skincare marketing and the responsibility for business owners who still use overclaim sentences. The research method used is normative research with statutory and conceptual approaches. Data collection is done by document study and interviews. The research data was analyzed descriptively qualitative. The results showed that business owner provide information on skincare products by using overclaim sentences as a result containing false advertising and not meeting consumer information standards in product sales. The use of overclaim sentences used in advertising skincare products results in contradiction with applicable regulations, such as consumer rights, business obligations, Article 3 paragraph (2) of BPOM Regulation Number 3 of 2022, and Article 3 of BPOM Regulation Number 32 of 2021. Business owners in the use of overclaims have clearly caused material losses in the form of losses to money spent and immaterial losses in the form of damage to the skin and emotional disappointment so that business actors must be responsible for these losses. The liability of business owners has been explained in Articles 19-20 of the GCPL, Articles 1365-1367 of the KUHPer, and BPOM Regulation Number 3 of 2022 explains the sanctions.